Controlling of the Quantum Dot LED Dynamics with a Small Optical Feedback Strength - Rekabie, Hussein A. Al; Husseini, Hussein B. Al (Journal of Applied Nonlinear Dynamics, 2026)
In this work a four-variable dimensionless model of a quantum dot light emitting diode (QDLED) under optical feedback effect is studied. The bifurcations of these dynamics is fully determined by the increasing the optical feedback strength OFBS. Our results show that small OFBS leads to a selection of QDLED dynamics. Increasing of the τ leads to increase both in region of the double period and the chaos. Otherwise, bias dominates the course of photons. Adding the grating mirror as a special technique stabilize the oscillation of a QDLED. It is worth mentioning that we did not get a perfect behavior except using this technique. Delayed feedback and turn-on dynamics are studied. Results show that there is no change QDLED dynamics because of controlling the bias current on the behavior of photons and the effect of delay forces the system to enter the state of chaos while the turn-on dynamics of the QDLED structure show damping of the relaxation oscillations and the increase of phase shift with increasing both of OFBS and delay time. Dependence the outset of chaos on the linewidth enhancement factor is examined.